Hukum Menjama’ Sholat karena Resepsi Manten, Karnaval dan Kebanjiran - Muslih, Ahmad (Prodi Pendidikan Agama Islam IAINU Kebumen, 2024)
This study aims to examine the ruling on combining prayers (jamak) in the context of wedding receptions, carnivals, and floods based on the views of classical and contemporary scholars. The method used is a literature review with qualitative descriptive analysis of fiqh literature, the Qur'an, hadith, and fatwas from scholars of various schools of thought. Jamak prayer refers to the combination of two different prayers performed in one time, such as Dhuhr with Asr or Maghrib with Isha. Generally, activities like wedding receptions and carnivals do not meet the masyaqqah (hardship) criteria that allow for combining prayers, according to the majority of scholars, thus excluding them from rukhshah (concessions). However, scholars such as Ibn Sirrin, al-Qaffal, Abu Ishaq al-Marwazi, and Imam al-Nawawi permit combining prayers due to extreme busyness, provided it does not become habitual. Additionally, scholars like Imam Ahmad, Ibn Taymiyyah, and Sheikh Ibn Uthaymeen allow jamak prayer during emergencies, such as floods.